Formalização do conjunto dos números racionais e alguns jogos com frações - Aveiro, José Carlos [UNESP] (2015)
This work presents the formal construction of the rational numbers obtained from the set of the integers numbers, thus explaining why some procedures and algorithms are used in the learning of rational numbers. Also, some games that can be used in the classroom to teach representation forms, equivalence, operations (addition, subtraction, multiplication, division) and comparison of fractions. Thus, seeks to present a teaching proposal of the fractions in order to make with the students to can engage in learning this topic